Fighting depreciation and inflationary pressures - Vasily Astrov (The Vienna Institute for International Economic Studies (wiiw), 2024)
The Russian authorities have been battling strong depreciation pressures, with the rouble having lost around 30% of its value since early 2023 (and inflationary pressures having risen strongly). The main reason for this is the declining supply of foreign exchange from foreign trade transactions, due to (i) a steady rise in the share of export contracts denominated in roubles, and (ii) the declining share of export earnings in foreign currency converted into roubles. To address the latter problem, on 16 October the authorities imposed a surrender requirement for export proceeds, which has proved highly effective at stabilising the exchange rate. However, despite this and a sharp rise in the policy rate of 7.5 pp in total since June, inflation has continued to accelerate, reflecting the ongoing expansionary fiscal stance, but also the lengthy nature of some monetary transmission mechanisms.
Keywords: E31; E5; F31; F32; 330; surrender requirement; exchange rate; inflation; credit growth